Impact of a multiple birth on maternal mental health and early mother-infant interactions: implications for information provision in IVF treatment - Beer, Charlotte Emma (2008)
One in four IVF pregnancies is a twin birth. This research explored the impact of a multiple IVF birth on maternal mental health and examined whether twin status conferred additional risk for poor mother-infant interaction and parenting stress following a premature birth. It further surveyed factors which had influenced couples' decisions regarding embryo transfer.